EFEKTIVITAS PENGGUNAAN E-LEARNING BERBASIS EDMODO TERHADAP HASIL BELAJAR FISIKA SISWA SMA NEGERI 2 TONDANO KELAS XI PADA MATERI SUHU DAN KALOR - Feyka Sigar; Ferdy Dungus; Alfrits Komansilan (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
This study aims to determine the effectiveness of the Edmodo learning media on the physics learning outcomes of SMA N 2 Tondano class XI students on the material of temperature and heat. This study uses experimental methods and the design used is the Posttest Only Control Group Design. The experimental class applies Edmodo learning media and the control class without using Edmodo learning media. After the learning process was carried out, the research data was then taken based on the posttest and stated that the average posttest score for the experimental class was 80.5, while the posttest average for the control class was 67.5. So the student learning outcomes or posttest experimental class students are higher than the posttest results of control class students. From these data, normality test and data homogeneity test were carried out and the results of the normality test showed that the data was normally distributed, as well as the homogeneity test stated that the two classes were homogeneous, then t-test was carried out and the results obtained were tcount of 3.87828 and ttable of 1.68595 thus H0 rejected and HA accepted. So it can be concluded that the application of Edmodo learning media is more effective because the average learning outcomes of experimental class students who use Edmodo media are higher than the average control class students' learning outcomes without using Edmodo media.